Security & Privacy Awareness & Concerns of Computer Users Posed by Web Cookies and Trackers - Almotiri, Smah Doeban E (Auckland University of Technology, 2022)
Web-cookies are an essential element across every website. Despite its importance for the growth and development of websites, cookies are associated with severe security and privacy risks. In numerous empirical studies, browser cookies have been proven to be insecure and vulnerable to cyber-attacks, resulting in compromised user data. Additionally, cookies breach users' online privacy in violation of the rules and laws that are in place to protect information privacy. The objectives of this study are to evaluate users' awareness of the threats of HTTP cookies and web trackers to data privacy and security as well as to determine the level of end-user privacy concerns regarding violations of this technology. An anonymous online survey addressed to adult Internet users on an international level has been developed. 34 questions, including one of which required accessing a website set up for this research, were completed by 471 respondents in order to evaluate respondents' levels of awareness of the risks of web tracking for the security and privacy of their personal data as well as determining their level of privacy concern. The findings of the survey analysis revealed that users are highly aware of the dangers that cookies represent to the security and privacy of personal data. Further, the findings demonstrated that there is a significant level of concern among respondents regarding the collection, usage, and storage of personal data via web tracking and cookies. These findings lead to the conclusion that local and international legislation should work to develop a framework with unified standards on an international level for governance and protection of privacy of users' data in the context of cookies and tracking in response to the concerns of users from different regions around the world about the practices of web trackers on their data that pose security risks and violate privacy.